APPLICATION OF LOCAL ANAESTHETIC CREAM AMONG CHILDREN, WHILE REMOVING ELEMENTS OF CONTAGIOSUM EPITHELIALE - E.I. Pil'gui; L.S. Namazova (Педиатрическая фармакология)
Contagiosum epitheliale is a wide spread dermatosis among younger and preteen children. The removal of elements is accompanied with the sensations of pain and conducive to the development of the adverse psychological and physiological responses of the child's body. In the present research the authors evaluated the efficacy of the local anaesthetic while removing elements of contagiosum epitheliale. The article presents etiology, clinical peculiarities, new methods of diagnostics and disease treatment.Key words: contagiosum epitheliale, anesthesia, pain evaluation, children.